The effect of osteoporosis on cochlear function in postmenopausal women: An observational study - Sağıroğlu, Saime; Koca, Tuba Tülay (Journal of Surgery and Medicine, 2018)
Aim: Hearing loss and osteoporosis are common geriatric syndromes. Evidence suggests that osteoporosis may have an effect on cochlear function in a small number of clinical trials. Here, cochlear function in osteoporosis patients was assessed by otoacoustic emission test measurements. Methods: The study designed as cross-sectional and observational. Forty female patients were included in the postmenopausal period at the age of 40-75 years. Age, body mass index (BMI), vitamin D level were recorded in all patients. Audiometric threshold testing was used to measure air- and bone-conduction hearing sensitivity. Bone mineral density (BMD) of the hip and vertebra was measured using dual-energy X-ray absorptiometry (DEXA). According to vertebra L1-4 t score <-2.5 osteoporosis, -2.5 to -1 osteopenic, the group divided into two and all parameters were compared. Transiently evoked (TE), and distortion-product (DP) otoacoustic emissions were recorded. Results: The mean age of the whole group was 58.6 ± 7.9 years. Accordingly, TE left was significantly different in the higher frequency in the osteopenic group at 0.75 Hz (p = 0.015). In audiometric tests, only the osteopenic group at 6,000 dB was significantly different in the higher frequency of both ears (p = 0.049 / p = 0.016). When the group divided into two according to femur t score <-1.0; TEright_3.5 (p = 0,04), TEright_overall (p = 0,030), TEleft_1.7.5 (p = 0,043) and TEleft_overall (p = p = 0.046), DPright_1 (p = 0.049) and DPleft_6 (p = 0.039) were observed to occur at higher frequencies in the osteoporotic group. Lomber t score was positively correlated with BMI (p = 0.042 / r = 0.288). BMI was lower in the osteoporotic group. The tympanogram results of all patients were Type A. The TE positivity rate (S / N> 3) was 60.8% and the DP positivity rate (S / N> 3) was 39.2%. Conclusion: According to hip BMD scores, osteopenic-osteoporotic (T scor <-1) group showed higher frequencies in both cochlear and hearing tests than normal subjects. The high frequencies in both OAET results and odiologic data in osteoporotic group support the adverse effect of osteoporosis on cochlear and hearing function. Individuals with hearing loss should be screened for osteoporosis.